Peningkatan Kemampuan Stakeholder Desa Jati Mulyo Kecamatan Jati Agung Kabupaten dalam Penyusunan Peraturan Desa tentang Pengelolaan Sampah - Syarifudin, Ahmad; Toto Andri Puspito; Diki Hermawan; Sri Furyani; Lisa Safitri; Lyana Allawiyah; Farida (Wisanggeni: Jurnal Pengabdian Masyarakat, 2022)
Many people and business actors in waste transportation services throw garbage carelessly which pollutes the environment in Jati Mulyo Village, so a Perdes is needed to regulate the community. The purpose of this service apart from compiling village regulations on waste management is also to equip Jati Mulyo Village stakeholders in preparing village regulations. Using the service learning method this service was carried out for 3 days and has increased the knowledge, understanding of stakeholders and produced a Perdes legal product regarding waste management.